Randomized control trial evaluating the effectiveness of ear plugs in hearing loss in NICU preterm babies - Shingeri, Fathma Thahmi; Shriyan, Ashvij R.; Maben, Roshan Ann; Soans, Santosh T. (International Journal of Contemporary Pediatrics, 2020)
Background: The prevalence of hearing loss is higher in neonates admitted to NICU compared to the general population. Preterm babies are more vulnerable to the hearing damage due to their immature inner ear exposing them to various high frequency noises in the NICU to which they were not accustomed. Most NICU in India exceed the recommended sound levels. In order to reduce damage to the ears, foam-based earplugs are used to reduce the sound intensity reaching the ears of these premature babies. Methods: Babies admitted to NICU are allocated alternatively to receive earplugs or not. Cases are preterm babies with earplugs and controls are the ones without earplugs. The incidence of hearing loss is found by OAE testing of the ears at the end of NICU stay. Results: Out of 40 in each group, 6 babies in control group failed the OAE compared the 3 in the earplug group. Babies who did wear earplugs had longer period of NICU stay. Conclusions: Use of earplugs in babies admitted to NICU reduced the incidence of hearing loss and also length of NICU stay.